HIV/AIDS and the forgotten majority : a gendered perspective of states' fulfillment of the 2001 Declaration of Commitment on HIV/AIDS amongst refugee populations. - McBride, Sindi-Leigh Tenielle (My University, 2011)
Refugees in prolonged states of exile remain neglected and excluded from the international political agenda, in particular refugee women. This research attempts to solve this problem by focusing on HIV/AIDS as a security threat to this group. It recognizes a synergy between protracted displacement, gender and HIV/AIDS and examines the marginalization of refugee women and how this contributes to their vulnerability to infection. This is done by analysing the degree to which host states, Kenya and Tanzania acting as case studies, comply with their international commitments, especially the 2001 UNGASS Declaration of Commitment on HIV/AIDS, in their National Strategic plans for HIV/AIDS and by examining their responses to the socio-economic factors of vulnerability. It also analyses the role played by the international refugee regime, in particular the United Nations High Commissioner for Refugees. It looks at how vulnerability to infection can be mitigated amongst refugee women. Key findings include that refugees in protracted states of displacement are marginalized by the host state due to their legal status as refugees and are neglected within the host states’ National Strategic Plans on HIV/AIDS and that inadequate levels of compliance to the relevant instruments of international law, in particular the Declaration of Commitment on HIV/AIDS, has resulted in host states failing refugee women.